2016
DOI: 10.1007/s10741-016-9587-y
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and cognitive function in patients with heart failure: a systematic review and meta-analysis

Abstract: Cognitive impairment and dementia are established complications of heart failure (HF) in adult patients and impair medication adherence and self-care. Atrial fibrillation (AF) is suggested to play an independent role in the cognitive decline in patients with HF. The objective of this systematic review was to assess the effect of AF on cognitive function in these patients. Medline (PubMed), Scopus, and the CENTRAL databases were queried from their inception up to April 30, 2016. The search included primary rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 66 publications
3
30
0
Order By: Relevance
“…Nevertheless, a large study reported that there was no difference in the longitudinal strain between patients without albuminuria and controls [ 21 ]. Additionally, the use of the STE method to assess myocardial strain has several limitations, including a lower signal-to-noise ratio, weak acoustic windows, and through-plane motion artifacts [ 22 , 23 ]. Furthermore, CMR tissue-tracking technology can assess cardiac deformation parameters with post-processing for cine images, which have a higher signal-to-noise ratio, and utilizes routine cine images without requiring any additional scan time [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a large study reported that there was no difference in the longitudinal strain between patients without albuminuria and controls [ 21 ]. Additionally, the use of the STE method to assess myocardial strain has several limitations, including a lower signal-to-noise ratio, weak acoustic windows, and through-plane motion artifacts [ 22 , 23 ]. Furthermore, CMR tissue-tracking technology can assess cardiac deformation parameters with post-processing for cine images, which have a higher signal-to-noise ratio, and utilizes routine cine images without requiring any additional scan time [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, information obtained from studies can guide upcoming researches and provide well-being procedures for effective self-management interventions of AF [1,3,4]. Therefore it is required to improve and recover the life condition of patients with chronic diseases including AF.…”
Section: Biomedical Research 2018; 29 (12): 2484-2489mentioning
confidence: 99%
“…Atrial fibrillation (AF) as the most common cardiac arrhythmia in 1-1.5% of general population [1]. The prevalence rate of AF is 0.5% in individuals aged 40-50 years old to 15% in 80 years old with higher risk of morbidities in men than in women [2,3]. It is associated with a five-fold greater risk of thromboembolism and stroke and other complications including neurologic injury, organ failure, and emergency department (ED) re-admissions [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Although reduction in cardiac performance remains an important and impactful complication of arrhythmia, there seems to be increasing evidence that AF is also independently associated with cognitive decline and dementia even without clinical history of stroke [1,[4][5][6][7]. is effect was revealed in AF patients both with and without coexisting heart failure [6,8,9]. However, pathogenesis of cognitive dysfunction in AF patients is still in discussion.…”
Section: Introductionmentioning
confidence: 99%